Pengaruh Campuraan Bakteri Pelarut Fosfat dan Bakteri Penambat Nitrogen terhadap Pertumbuhan Tanaman Jagung pada Lahan Kelapa Sawit (Elaeis guineensis Jacq.) Menghasilkan - Azzahra, Talitha Novania; Suherman Viktor Zhar, Cucu; Ratna Dewi Anjarsari, Intan (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Intercropped farming utilizez used open spaces as an alternative to making empty land more productive. In certain periods, oil palm plantations have open spaces that can be used for planting intercropped plants. The problem is, in general, that oil palm plantations are planted on marginal land, such as inceptisol that is weak in phosphate, so if they are planted with palm oil, it is necessary to provide fertilizer with the main macro element content for palms to grow optimally, such as phosphorus (P) and nitrogen (N). Efforts can be made to meet the P and N requirements by applying combinations of microorganisms such as phosphate solubilizing bacteria (PSB) and nitrogen-fixing bacteria (NFB). The study aims to find out the effect of various dosages of PSB and NFB combinations on the growth and yield of corn crops, as well as the effect of corn crops on the growth and physiology of palm oil crops. The experiment was conducted at the Ciparanje Experimental Farm, Faculty of Agriculture, Padjadjaran University, January to April 2024. The study used a randomized block design (RBD) with six treatments repeated four times. The treatments included the application of a combination of Pseudomonas sp. and Azotobacter sp., which included: 10 kg/ha of PSB and NFB per plant, 20 kg/ha of PSB and NFB per plant, 30 kg/ha of PSB and NFB per plant, 40 kg/ha of PSB and NFB per plant, and 50 kg/ha of PSB and NFB per plant. Experimental results showed that the PSB and NFB mixture increased crop height 5.28%, stem diameter 3.19%, cob length 9.2%, cob diameter 9.8%, dried weight by 100 seeds 14.5%, and dried weight by corn plant 33.46%. The 40 kg/ha and 50 kg/ha dose of PSB and NFB per plant is the most efficient dose for the growth and of palm oil crops producing 2.